2017
DOI: 10.1007/s10562-017-2249-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Desorption of Methanol and Dimethyl Ether Over ZSM-5 Catalysts

Abstract: The desorption of methanol and dimethyl ether has been studied over fresh and hydrocarbon-occluded ZSM-5 catalysts with Si/Al ratios of 25, 36 and 135 using a temporal analysis of products reactor. The catalysts were characterized by XRD, SEM, N 2 physisorption and pyridine FT-IR. The crystal size increases with Si/Al ratio from 0.10 to 0.78 µm. The kinetic parameters were obtained using the Redhead method and a plug flow reactor model with coupled convection, adsorption and desorption steps. ZSM-5 catalysts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(99 citation statements)
references
References 57 publications
7
92
0
Order By: Relevance
“…They are suppressed due to negligible intramolecular collisions under vacuum conditions . In a previous contribution, we also showed that the rates of methanol and DME adsorption and desorption are limiting compared to intraparticle mass transport contributions. In Section 4, we show that these rates compete with the rate of transformation of intermediates during the conversion of DME to primary olefins.…”
Section: Methodsmentioning
confidence: 62%
See 4 more Smart Citations
“…They are suppressed due to negligible intramolecular collisions under vacuum conditions . In a previous contribution, we also showed that the rates of methanol and DME adsorption and desorption are limiting compared to intraparticle mass transport contributions. In Section 4, we show that these rates compete with the rate of transformation of intermediates during the conversion of DME to primary olefins.…”
Section: Methodsmentioning
confidence: 62%
“…The ammonium form of the fresh ZSM‐5 catalyst with a Si/Al ratio of 25, purchased from Zeolyst International, has a crystallite size of 0.10 ± 0.02 μm and an average particle size of 30 μm . The ZSM‐5 catalysts are here referred to as ZSM‐5 (25).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations